2022
DOI: 10.1177/21925682221078239
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Intraoperative CT Hounsfield Unit Values for the Assessment of Bone Quality in Patients Undergoing Lumbar Interbody Fusion

Abstract: Study Design Retrospective Cohort Study Objective To evaluate the accuracy of intraoperatively measured computed tomography (CT) Hounsfield unit (HU) values by comparison with preoperative CT HU values and to compare the radiation exposure between preoperative and intraoperative CT scans. Methods HU values of lumbar vertebrae were measured and compared between preoperative and intraoperative CT scans in patients undergoing lumbar interbody fusion. In patient group one, Canon CT scanners were used preoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A total of 86.5% of patients suffered from a proximal adjacent ) and a Mentally Health Component Summary Score (MSC) of 30.9 (18.4-44.9) of the study population. Mood state analysis showed a median of ADS-K depression score of 16 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Concerning radiographical determined parameters, the two groups showed no significant differences.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A total of 86.5% of patients suffered from a proximal adjacent ) and a Mentally Health Component Summary Score (MSC) of 30.9 (18.4-44.9) of the study population. Mood state analysis showed a median of ADS-K depression score of 16 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Concerning radiographical determined parameters, the two groups showed no significant differences.…”
Section: Resultsmentioning
confidence: 89%
“…Disc heights and diameters of spinal canals were measured in preoperative MRI scans. For osteoporosis assessment, hounsfield units (HUs) of adjacent vertebral body were determined in preoperative CT-scans with 1 mm slices [14]. Therefore, an oval region of interest was placed over axial image of the vertebral body of the adjacent corporal body.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Moreover, HU measured at a region of interest (ROI) of the screw trajectory presents the approximate BMD and correlates strongly with insertion torque and implant stability in vitro and in vivo studies. [23][24][25][26] Furthermore, Han et al 27 demonstrated that HU values on C2-3 segments indicate a more reliable BMD level than those on C4-7 segments, and HU values of cervical CT provided reliable information regardless of measured sections, age, sex, and degree of degeneration. Therefore, the BMD, insertion torque, and implant stability of translaminar screw can be approximately compared between patients with and without BI using the HU values measured on C2 laminae.…”
Section: Introductionmentioning
confidence: 99%